Culinary Recipe Recommendation based on Text Analytics - Hong, Jiheon; Lee, Heejung (International Journal of Engineering and Technology, 2018)
Many researchers and practitioners have studied the recipe recommendation, and that problem is not only to find the tasty dishes based on the individualâ€™s preference, but also to generate new ones. In the digital age, understanding and utilizing text data is one of the most important part in the knowledge discovery. In this paper, we proposed how to use text analysis in the recipe recommendation problem and provided the insights to design new recipes.Â